Two Cases of Duodenal Ulcers That Developed after Transcatheter Procedures for Unruptured Visceral Artery Aneurysms - Masaya Iwamuro; Yusuke Kawai; Mayu Uka; Yusuke Matsui; Takao Hiraki; Yoshiro Kawahara; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
Herein, we report two cases of duodenal ulcers that developed after transcatheter procedures for the treatment of unruptured artery aneurysms. Both patients recovered after the administration of nothing by mouth, intravenous fluids, and proton-pump inhibitors. Notably, the duodenal ulcer was unchanged in one patient six days after endovascular treatment and improved in the other patient 13 days after angiography. These cases suggest that conservative treatment is acceptable in patients with duodenal ischemia that develops as an adverse effect of endovascular procedures. The usefulness of esophagogastroduodenoscopy in such patients has also been highlighted.